Penggunaan Bahasa Pada Anak Usia Dini di Kelurahan Bulukunyi Kecamatan Polongbangkeng Selatan Kabupaten Takalar (Study Program of Indonesian Language Education, Faculty of Languages and Literature, Universitas Negeri Makassar, 2023)
This study aims to describe the use of language in early childhood in the home and school environment in Bulukunyi Village, South Polongbangkeng District, Takalar Regency. This type of research is classified as qualitative research, which is analysed descriptively. The data in this study are the utterances used by early childhood while playing in the home and school environment. The key instrument and used tools in the form of videos and cameras. The source of data in this study is class B students of Hilmawan Kindergarten, Takalar Regency with 23 students. This research data is data obtained from the results of observations and interviews of researchers on students of Hilmawan Kindergarten, Takalar Regency. The results show that the use of language in early childhood in Bulukunyi Village, Polongbangkengeng Selatan District, Takalar Regency uses two languages, namely Makassar language and Indonesian language which is called code mix. The results obtained, early childhood is more dominant in using non-standard Indonesian, but the position of the use of Makassar language can still be declared not extinct because early childhood when communicating still uses code mix.